Aerosol generation rates for showerheads. (September 2019) - Zhou, Yang; Mui, Kwok Wai; Wong, Ling Tim; Tsui, Pak Hei; Chan, Wing Ki
Aerosolization of water from discharging water appliances provides a transmission medium for Legionnaires' disease. The quantity of aerosolized droplets influences the infection of Legionnaires' disease. This study investigates the aerosol generation rates of four sample showerheads experimentally in a mechanically ventilated test chamber, assisted by computational fluid dynamics simulations. The results show that aerosol mass generation rate decreases with the showerhead resistance factor but increases with the water supply pressure, nozzle area ratio, flow rate, spray jet velocity, momentum and force. There is no significant correlation between aerosol mass generation rate and water spray uniformity ( p  > 0.05, t -test). Furthermore, the aerosol mass generation rates and aerosol particle generation rates determined for the sample showerheads are in the ranges of 1.42 × 10 −5 to 5.52 × 10 −5  g s −1 and 0.35 × 10 6 to 1.35 × 10 6 particles s −1, respectively. Practical application : The proposed expression of aerosol generation rate can be the referenced guidance for future showerhead design to limit the aerosol generation rate.